Ensemble global warming simulations with idealized Antarctic meltwater input - Park, Wonsun; Latif, Mojib (Climate Dynamics, 2019)
The Earth will exhibit continued global surface warming in response to a sustained increase of atmospheric carbon dioxide (CO2) levels. Massive meltwater input from the Antarctic ice sheet into the Southern Ocean could be one consequence of this warming. Here we investigate the impacts which this meltwater input may have on Earth’s surface climate and ocean circulation in a warming world. To this end a set of ensemble experiments has been conducted with a global climate model forced by increasing atmospheric CO2-concentration and an idealized Antarctic meltwater input to the Southern Ocean with varying amplitude and spatial pattern. As long as the atmospheric CO2-concentration stays moderate, i.e. below approximately twice the preindustrial concentration, and if a strong meltwater forcing of either 0.05 or 0.1 Sv is applied, enhanced Antarctic sea–ice cover and surface air temperature cooling over most parts of the Southern Ocean is observed. When the atmospheric CO2-concentration becomes larger than twice the preindustrial concentration, the meltwater only plays a minor role. The Antarctic meltwater drives significant slowing of the Southern Ocean meridional overturning circulation (MOC). Again, the meltwater influence only is detectable as long as the CO2-forcing is moderate. Much larger MOC changes develop in response to highly elevated atmospheric CO2-levels independent of whether or not a meltwater forcing is applied. The response of the Antarctic circumpolar current (ACC) is nonlinear. Substantial and persistent ACC slowing is simulated when solely the meltwater forcing of 0.1 Sv is applied, which is due to the halt of Weddell Sea deep convection and subsequent collapse of the Southern Ocean MOC. When the increasing atmospheric CO2-concentration additionally drives the model the ACC partly recovers in the long run. The partial recovery is due to strengthening westerly wind stress over the Southern Ocean, which intensifies the Ekman Cell. This study suggests that Southern Hemisphere climate projections for ...